Collaboration Among Competing Managed Care Organizations for Quality Improvement : Summary of a Conference, November 13, 1997 - Donaldson, Molla S. (Compass series (Washington, D.C.), 1999)
Session 1: Conceptual issues in collaboration -- Session 2: Panel presentations -- Session 3: Examples of collaboration -- Biographies of speakers -- Conference agenda.